2019
DOI: 10.1371/journal.pone.0222495
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism rates in individuals receiving community sentences: A systematic review

Abstract: ObjectiveWe aimed to systematically review recidivism rates in individuals given community sentences internationally. We sought to explore sources of variation between these rates and how reporting practices may limit their comparability across jurisdictions. Finally, we aimed to adapt previously published guidelines on recidivism reporting to include community sentenced populations.MethodsWe searched MEDLINE, PsycINFO, SAGE and Google Scholar for reports and studies of recidivism rates using non-specific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Within 3 years, nearly 40% of former prisoners incurred a violation of parole or probation or an arrest for a new offence, and within 5 years, nearly half did (Durose & Antenangeli, 2021). Although recidivism prevalence estimates are particularly high among U.S. parolees/probationers, recidivism estimates are substantively comparable to studies of former prisoners selected from 20 nations who are now on community supervision (Yukhnenko et al, 2019). In diverse nations, including Australia, Canada, Denmark, Finland, the Netherlands, New Zealand, and the United Kingdom, between 20% and 40% of individuals serving community-based sentences were reconvicted of a new crime within 2 years.…”
Section: Introductionmentioning
confidence: 67%
“…Within 3 years, nearly 40% of former prisoners incurred a violation of parole or probation or an arrest for a new offence, and within 5 years, nearly half did (Durose & Antenangeli, 2021). Although recidivism prevalence estimates are particularly high among U.S. parolees/probationers, recidivism estimates are substantively comparable to studies of former prisoners selected from 20 nations who are now on community supervision (Yukhnenko et al, 2019). In diverse nations, including Australia, Canada, Denmark, Finland, the Netherlands, New Zealand, and the United Kingdom, between 20% and 40% of individuals serving community-based sentences were reconvicted of a new crime within 2 years.…”
Section: Introductionmentioning
confidence: 67%
“…This review is an update of three systematic reviews ( Fazel & Wolf, 2015 ; Yukhnenko, Sridhar, & Fazel, 2019 ; Yukhnenko, Wolf, et al, 2019 ). We searched SAGE, MEDLINE, EMBASE, PsycINFO, PsycARTICLES, and Web of Science bibliometric databases using search terms related to criminal recidivism.…”
Section: Methodsmentioning
confidence: 99%
“…Recidivism rates are routinely collected by most countries and reported by specific governmental agencies (see Federal Statistical Office, 2015 ; Ministry of Justice, 2023 ; SPAC, 2018 ). Recidivism is measured in different ways, and previous reviews have shown that the 2-year reconviction rate is most commonly reported outcome in individuals released from prisons ( Yukhnenko, Sridhar, & Fazel, 2019 ) and those completing community sentences ( Yukhnenko, Wolf, Blackwood, & Fazel, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of access to financial support can significantly impact women's ability to successfully navigate the reentry process and result in a higher likelihood of returning to crime as a means of survival. Although it can be tricky comparing international recidivism rates, because countries often use different terms to measure recidivism and varying lengths of time to re-offense, evidence suggests that 9-35% of women are reconvicted within one to two years (Yukhnenko et al, 2019). Overall, given that women face unique experiences pertaining to victimization, mental health, and substance abuse coupled with their role as primary care provider to their children and returning to impoverished neighborhoods post-release, many struggle to successfully navigate integration into the free world.…”
Section: Women and Reentrymentioning
confidence: 99%